No association between ACTN3 R577X and ACE I/D polymorphisms and endurance running times in 698 Caucasian athletes - Ioannis Papadimitriou; S. J. Lockey; Sarah Voisin; Adam J. Herbert; Fleur C. Garton; Peter J. Houweling; Paweł Cięszczyk; Agnieszka Maciejewska; Marek Sawczuk; Myosotis Massidda; Carla Maria Calò; Irina V. Astratenkova; et al. (2018)
Studies investigating associations between ACTN3 R577X and ACE I/D genotypes and endurance athletic status have been limited by small sample sizes from mixed sport disciplines and lack quantitative measures of performance. Aim: To examine the association between ACTN3 R577X and ACE I/D genotypes and best personal running times in a large homogeneous cohort of endurance runners. We collected a total of 1064 personal best 1500, 3000, 5000 m and marathon running times of 698 male and female Caucasian endurance athletes from six countries (Australia, Greece, Italy, Poland, Russia and UK). Athletes were genotyped for ACTN3 R577X and ACE ID variants. There was no association between ACTN3 R577X or ACE I/D genotype and running performance at any distance in men or women. Mean (SD) marathon times (in s) were for men: ACTN3 RR 9149 (593), RX 9221 (582), XX 9129 (582) p = 0.94; ACE DD 9182 (665), ID 9214 (549), II 9155 (492) p = 0.85; for women: ACTN3 RR 10796 (818), RX 10667 (695), XX 10675 (553) p = 0.36; ACE DD 10604 (561), ID 10766 (740), II 10771 (708) p = 0.21. Furthermore, there were no associations between these variants and running time for any distance in a sub-analysis of athletes with personal records within 20% of world records. Thus, consistent with most case-control studies, this multi-cohort quantitative analysis demonstrates it is unlikely that ACTN3 XX genotype provides an advantage in competitive endurance running performance. For ACE II genotype, some prior studies show an association but others do not. Our data indicate it is also unlikely that ACE II genotype provides an advantage in endurance running.